Research on the Novel Primary and Secondary Embedded Deployable Cage Mechanism - Liu Ziyu; Hang Lubin; Bai Lele; Huang Xiaobo; Wang Mingyuan; Chen Junrong; Li Sulong; Zhang Pengcheng (Jixie chuandong)
Cage aquaculture is an important strategic direction for marine aquaculture. Aiming at the problems that the existing offshore cages are difficult to adjust the breeding areas adaptively to optimize the ecological environment and the difficulty in transportation due to their large size， a novel primary and secondary embedded deployable offshore cage is proposed which the over-constrained spatial mechanisms and planar compliant mechanisms are respectively adopted as the primary and secondary cages. A closed-loop cable-driven module is designed to deploy the cage through the pull and release of the cable. Then， the evolution of the dimension constraint types of the threefold-symmetric Bricard mechanism which forms the primary cage mechanism is investigated. The geometric invariant characteristics that three symmetric planes intersecting at a determined line are revealed so that the cage driven mechanism with the symmetrically plane intersecting line as the axis of mechanism folding is constructed. Further， by establishing the kinematics equation of the primary cage mechanism， the relationship between the driven angle and corresponding open state of the cage can be derived from geometric projection on the symmetric planes. The novel primary and secondary embedded deployable cage mechanism with large deployable ratio can provide new thread for the design of offshore cages.